A Cross-sectional Survey Assessing Knowledge, Attitude, and Practice Regarding Oral Cancer among Private Medical and Dental Practitioners in Bhubaneswar City - Jnaneswar, Avinash; Goutham, Bala Subramanya; Pathi, Jayashree; Jha, Kunal; Suresan, Vinay; Kumar, Gunjan (Indian Journal of Medical and Paediatric Oncology, 2017)
Introduction: Oral cancer is a public health problem giving rise to a great number of disabilities and deaths, but the possibility of survival is astonishingly higher when detected early. Health professionals therefore have an important role and responsibility in the prevention and early detection of oral cancer. They should be in a position to identify all suspicious lesions and to search for specialist opinion as promptly as possible when unsure, while also referring to the most appropriate discipline. Aim: This study aimed to assess the knowledge, attitude, and practices (KAPs) regarding oral cancer among private medical practitioners (MPs) and private dental practitioners (DPs). Materials and Methods: A cross-sectional, questionnaire-based study was conducted among 334 MPs and 201 DPs in Bhubaneswar. A self-designed, close-ended questionnaire containing 28 items was delivered to the practitioners in their clinics. Correlation between KAP among MPs and DPs was done by Karl Pearson's correlation coefficient test. Student's t-test was used to compare the KAP among the practitioners. Results: Of the 535 practitioners approached, 513 filled the questionnaire with a response rate of 95.88%. Significantly, the mean knowledge index was higher among DPs (10.96 ± 1.85). The attitude index was higher in the MPs (6.89 ± 1.11), and the practice index was higher among the DPs (4.95 ± 0.91). Conclusion: The study puts forward the need of further training for both MPs and DPs to increase awareness and to strengthen their abilities to diagnose potentially cancerous intra-oral lesions.
Keywords: Dental practitioners; early detection; medical practitioners; oral cancer